2011
DOI: 10.1158/0008-5472.sabcs11-s3-1
|View full text |Cite
|
Sign up to set email alerts
|

S3-1: Update of International Breast Cancer Study Group Trial 23-01 To Compare Axillary Dissection Versus No Axillary Dissection in Patients with Clinically Node Negative Breast Cancer and Micrometastases in the Sentinel Node.

Abstract: Introduction and Study Design For patients (pts) with a metastatic sentinel node (SN), axillary dissection is standard treatment to achieve optimal locoregional control. However, for many pts the SN is the only positive node and for pts with minimal SN involvement, axillary dissection (AD) may be overtreatment. IBCSG Trial 23-01 was designed to determine whether AD is necessary in pts with minimal SN involvement (defined as one or more micrometastatic (≤2 mm) SNs) and tumor ≤5 cm. Consenting eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 0 publications
2
16
0
2
Order By: Relevance
“…27 In the International Breast Cancer Study Group 23-01 trial, patients with SLN micrometastasis were randomly selected for completion ALND or no further surgery. 28 The trial did not exclude patients planned for mastectomy, and investigators reported that 25 % underwent mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…27 In the International Breast Cancer Study Group 23-01 trial, patients with SLN micrometastasis were randomly selected for completion ALND or no further surgery. 28 The trial did not exclude patients planned for mastectomy, and investigators reported that 25 % underwent mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…15 The enrollment was prematurely closed, because the projected time to complete accrual was too long and the aggregate event rate much lower than anticipated. At a median follow-up of 57 months, the AD vs. no-AD arms showed no difference in the 5-year rate for disease-free (87.3 vs. 88.4 %; p = 0.48) and overall survival (97.6 vs. 98 %; p = 0.35).…”
Section: Discussionmentioning
confidence: 99%
“…At a median follow-up of 57 months, the AD vs. no-AD arms showed no difference in the 5-year rate for disease-free (87.3 vs. 88.4 %; p = 0.48) and overall survival (97.6 vs. 98 %; p = 0.35). 15 The ACOSOG Z0011 is the first trial with a no treatment arm in SLN-positive patients to be fully reported. 6 Overall, its results support the concept that AD may not be necessary in this subset of patients, at least when only limited axillary tumor load is present and radiotherapy to the breast is administered after breast-preserving surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Galimberti et al étaient cependant prudents dans les indications d'abstention du curage axillaire en cas de ganglion sentinelle micrométastatique [51]. Dans cette série monocentrique de 377 patientes atteintes d'un ganglion sentinelle micrométastatique qui n'ont pas eu de curage axillaire complémentaire pour des raisons variables, il a été évalué les survies globales et sans récidive ainsi que le taux de récidive axillaire.…”
Section: Curage Axillaire : L'abstention De Curage Axillaire Complémeunclassified